Pembelajaran Al-Qur`an Dengan Metode Talqin Di Masjid Abdullah bin Mas`ud dan Masjid Miftahul Hidayah Cibodas - Rabbani, Muhammad Aqil; Dhiyaudin; Habibun; Sani, Asrul; Firmansyah, Hanif (Pusat Penelitian dan Pengabdian Masyarakat STIQ ZAD Cianjur, 2023)
Qur'anic learning with the Talqin method is Qur'anic learning in which an Ustadz or Qur'anic teacher dictates the recitation of the Qur'an to the participants in accordance with the rules of tajweed, Waqaf rules, and Ibtida. This article aims to describe the effectiveness of learning the Qur'an with the Talqin method. This service reveals the effectiveness of learning the Qur'an using the Talqin method to TPQ students at the Abdullah bin Mas`ud Mosque and the Miftahul Hidayah Cibodas Cianjur Mosque. The results of this service show the effectiveness of the Talqin method for Qur'an learners at the Abdullah bin Mas`ud Mosque and the Miftahul Hidayah Cibodas Mosque.